2003
DOI: 10.1097/00000542-200304000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Cardiac Output Measurement Using Partial Carbon Dioxide Rebreathing Is Less Accurate at Settings of Reduced Minute Ventilation and when Spontaneous Breathing Is Present

Abstract: During controlled mechanical ventilation, minute ventilation rather than tidal volume affected the accuracy of cardiac output measurement using the partial carbon dioxide rebreathing technique. When spontaneous breathing is present, the carbon dioxide rebreathing technique is less accurate and increases spontaneous tidal volume and respiratory rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 0 publications
1
30
1
1
Order By: Relevance
“…While some investigators found close agreement with thermodilution [13, 28], others could not confirm these data [10, 14, 29]. Tachibana et al [11] found only poor agreement in spontaneously breathing patients and proposed to restrict this technique to mechanically ventilated patients. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some investigators found close agreement with thermodilution [13, 28], others could not confirm these data [10, 14, 29]. Tachibana et al [11] found only poor agreement in spontaneously breathing patients and proposed to restrict this technique to mechanically ventilated patients. …”
Section: Discussionmentioning
confidence: 99%
“…Until recently, only a partial CO 2 rebreathing system, whose reliability and accuracy are controversial even under stable hemodynamic and respiratory conditions, was commercially available [10]. Changes in the ventilatory setting [11, 12] and high intrapulmonary shunt fractions [13, 14] impacted on the accuracy of the measurements as well. Overall, the value of partial CO 2 rebreathing seems to be at least limited under various clinical conditions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Th ere are several limitations to this device including the need for intubation and mechanical ventilation with fi xed ventilator settings and minimal gas exchange abnor malities [27]. Variations in ventilator settings, mechanicallyassisted spontaneous breathing, the presence of increased pulmonary shunt fraction, and hemodynamic instability have been associated with decreased accuracy [28]. Th us, this technique may be applied in a precisely defi ned clinical setting to mechanically ventilated patients only.…”
Section: Applied Fick Principlementioning
confidence: 99%
“…There are several limitations to this device, including the need for intubation and mechanical ventilation with fixed ventilator settings and minimal gas exchange abnormalities [30]. Variations in ventilator settings, mechanically assisted spontaneous breathing, the presence of increased pulmonary shunt fraction, and hemodynamic instability have been associated with decreased precision of the device [31,32]. In addition, validation studies have shown poor agreement between the NICO device and PAC [33,34].…”
Section: Applied Fick's Principlementioning
confidence: 99%